Компьютерное планирование пластических вмешательств методом деформации полигональной модели лица человека - Книгавко, Ю. В. (НПП ЧП «Технологический Центр», 2013)
The article presents the results of the development of the method of preoperative computer planning of surgical intervention on a human face to improve functional and aesthetic characteristics, which accelerates the planning process. The described method of the computer planning is based on the principle of three-dimensional modeling of polygonal models of the facial part of a person, using photogrammetry data or results of processing of the digital data of tomographic study of patient’s head. We have described the structural scheme of the software product and discussed some aspects of the development, permitting to implement effectively in real time the extrusive and intrusive deformations of the corresponding polygonal models, and to carry out the accompanying three-dimensional visualization. During the development when calculating the transformations of the rendered model we used the methods of polygonal representation of tomographic data, the method of spatial modeling of anatomical structures, the methods of linear algebra and analytical geometry. The result of the development is the creation of a new software product that can be used to optimize the procedure for solving a number of problems of computer planning in various areas of plastic medicine. Thus, the results of the work on a new method of computer planning of surgical intervention on the human face make it possible to optimize the solution of the problem.
Keywords: polygonal model; three-dimensional visualization; 3D modeling